2020
DOI: 10.1051/0004-6361/201937392
|View full text |Cite
|
Sign up to set email alerts
|

TRAPPIST-1: Global results of theSpitzerExploration Science Program Red Worlds

Abstract: Context. With more than 1000 h of observation from Feb. 2016 to Oct. 2019, the Spitzer Exploration Program Red Worlds (ID: 13067, 13175 and 14223) exclusively targeted TRAPPIST-1, a nearby (12 pc) ultracool dwarf star, finding that it is orbited by seven transiting Earth-sized planets. At least three of these planets orbit within the classical habitable zone of the star, and all of them are well-suited for a detailed atmospheric characterization with the upcoming JWST. Aims. The main goals of the Spitzer Red W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(121 citation statements)
references
References 133 publications
8
113
0
Order By: Relevance
“…K2; Howell et al 2014). Follow-up observations Ducrot et al 2018;Burdanov et al 2019;Ducrot et al 2020) later not only confirmed the existence of at least seven temperate, terrestrial-size planets around the star TRAPPIST-1, but also helped to better constrain their main properties (summarized in Table 1).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…K2; Howell et al 2014). Follow-up observations Ducrot et al 2018;Burdanov et al 2019;Ducrot et al 2020) later not only confirmed the existence of at least seven temperate, terrestrial-size planets around the star TRAPPIST-1, but also helped to better constrain their main properties (summarized in Table 1).…”
Section: Introductionmentioning
confidence: 88%
“…of . References: (1) , (2) , (3) Burgasser and Mamajek (2017), ( 4) Kane (2018) using Gaia DR2 parallaxes, (5) , ( 6) , ( 7) Ducrot et al (2020) for a null albedo, a synchronous rotation, and no atmosphere at all Fig. 1 Architecture of the TRAPPIST-1 system and evolution of the runaway greenhouse/atmospheric collapse limit for water (a.k.a.…”
Section: Constraints From the Stellar Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the atmosphere of planet d could be dominated by other atmospheric gases different from H 2 O-based mixtures, which could produce an extended atmosphere and increase the total planetary radius. Hydrogen-dominated atmospheres have been deemed unlikely as one of the possible atmospheric compositions for all planets in the TRAPPIST-1 system, both cloudfree (de Wit et al 2016(de Wit et al , 2018 and with high-altitude clouds and hazes (Grimm et al 2018;Ducrot et al 2020). Similarly, CH 4 -dominated atmospheres are not probable according to the photometry data of the Spitzer Space Telescope (Ducrot et al 2020).…”
Section: Alternative Atmospheric Compositionsmentioning
confidence: 99%